Acupuncture as a Complementary Therapy for Stroke Risk Reduction in Rheumatoid Arthritis - Hilde Juzeniene Torhild; Kjennerud Carlet; Linda Juzeniene Torhild (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease associated with increased inflammation and increased risk of stroke. In Norway, where acupuncture is widely practiced, there is growing interest in its potential role in reducing cardiovascular complications. This study explored the effectiveness of acupuncture in reducing stroke risk factors among RA patients and its potential integration into healthcare practice. Conducted in 2024 in Oslo, Bergen, and Trondheim, the study included 200 RA patients aged 18–75 years who met the 2010 ACR/EULAR criteria and received regular acupuncture treatment. Quantitative data were collected through clinical evaluation of blood pressure, inflammatory markers (CRP, TNF-α), and stroke risk indicators at baseline and post-treatment, while qualitative data were obtained through semi-structured interviews. The findings showed significant reductions in inflammatory markers and improved blood pressure regulation following acupuncture therapy. Participants also reported improved quality of life, supporting the role of acupuncture as a complementary therapy. These findings are in line with similar studies in Sweden but offer local insights specific to Norway. Mechanistically, acupuncture appears to reduce inflammation and improve vascular health through modulation of the autonomic nervous system. This study underscores the importance of integrating acupuncture into RA management to reduce cardiovascular risk. Future studies should focus on long-term effects, larger sample sizes, and explore a wider range of cardiovascular markers. Cost-effectiveness studies and assessment of cultural acceptability are also recommended to support its inclusion in the public health care system.